Stable fly (Stomoxys calcitrans) impacts on feedlot cattle - Martell, David (My University, 2026)
Stable flies are prolific blood-feeding pests of livestock worldwide, resulting in millions of dollars in loss of production annually. As few as five stable flies per animal can reduce feed efficiency and weight gain in beef cattle. Studies measuring the economic impact of stable flies usually correlate the number of flies per animal with individual production performance, which is time consuming and labor-intensive and, as such, is not readily used by producers when making fly control decisions. Due to the painful bites inflicted, cattle under fly pressure often exhibit stereotypic fly aversion behaviors including leg stamping, skin twitching, head tossing, tail swishing and bunching, referred to collectively as fly worry. This study aimed to determine if fly worry behavior could be used as a more producer-friendly metric to quantify economic impact and drive fly mitigation strategies in feedyards. Three feedyards with an average head count of 50,000, located in three different counties in Western Kansas were observed monthly during periods with and without stable fly activity. A small drone was flown overhead cattle pens at each facility monthly and still images were captured. Pen space occupancy, proportion standing, and proportion at the feed bunk were recorded and determined for each sampling event. When comparing high fly pressure pens (those adjacent to vegetation in which stable flies originate), and low fly pressure pens (located away from fly resting habitats), significant differences in animal behavior were observed during periods of fly activity. When sampled, high fly pressure pen animals had a lower proportion of cattle at the feed bunk, a higher proportion standing, and occupied less pen space area, indicating higher levels of bunching. Changes in behavior likely explain the higher feed-to-gain ratios observed in high fly pressure pens. This study concludes that cattle bunching behavior due to the presence of stable flies in summer months can be used to better quantify economic impact of stable flies and should be further explored.
Keywords: Stable flies; Stomoxys calcitrans; Feedyard cattle; Fly-worry behavior; Cattle bunching; Feed efficiency